Local Wisdom-Based Movable Book as A Teaching Material to Enhance Nationalism in the 21st Century - Wulandari, Medita Ayu; Senen, Anwar; Wardani, Duhita Savira; Kelana, Jajang Bayu (Jurnal Pendidikan Progresif, 2022)
Movable Book Local Wisdom-Based as Teaching Material to Increase Nationalism in the 21st Century. Objectives: This research investigates the effectiveness of movable book local wisdom based as a teaching material in improving students’ nationalism. Methods: Quasi-experiment was used with a non-equivalent control group design. The population of this study is the fourth-grade primary students. The data were measured using n-gain and independent t-test. Findings: The result shows that the n-gain of students’ nationalism in the experimental classes 1 and 2 were higher than the control class, such as 0.40, 0.39, and 0.29, with a moderate category for experimental classes and a low category for control class. Moreover, t-test results also showed that the value (p) was 0.000, which ≤ 0.05, so it significantly differences in students’ nationalism between experimental and control classes. Conclusion: Therefore, it can conclude that the movable book local wisdom-based teaching material can improve fourth-grade elementary students' nationalism character effectively. Keywords: 21st century, nationalism, local wisdom, teaching material, movable book.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202205